Women and Climate Vulnerability in Nadia District (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Climate change has emerged as a major challenge affecting rural communities across South Asia. In flood-prone regions of eastern India, environmental hazards such as floods, riverbank erosion, and irregular rainfall patterns have increasingly disrupted traditional livelihoods. These environmental transformations interact with existing social inequalities, producing differentiated impacts across gender and class. This article examines the relationship between climate vulnerability and women’s livelihoods in Nadia district of West Bengal. Located in the lower Gangetic plains and intersected by several rivers such as the Bhagirathi, Jalangi, and Churni, the district frequently experiences floods and riverbank erosion that threaten agricultural production and rural settlements. These environmental disruptions often disproportionately affect women because of their dependence on natural resources, their roles in household management, and their limited access to economic assets and decision-making institutions. This article will explores how environmental change has influenced women’s livelihood strategies, labour participation, and social mobility in Nadia district. The study argues that while climate vulnerability intensifies gender inequalities, women have also developed adaptive strategies including livelihood diversification, community organization, and traditional ecological knowledge. Understanding the gendered dimensions of climate vulnerability is therefore essential for designing sustainable environmental policies and inclusive rural development strategies.